Improvement of percutaneous coronary intervention in patients with ischemic cardiomyopathy: a systematic literature review - Fozilov , Khurshid; Abdukomilov , Abdulatif (CARDIOLOGY OF UZBEKISTAN, 2025)
Aim. To evaluate the effectiveness of percutaneous coronary intervention (PCI) in patients with ischemic cardiomyopathy and identify opportunities for its improvement, as well as to conduct a comparative analysis with coronary artery bypass grafting (CABG).Materials and methods. A systematic search of medical literature published from 2017 to 2025 was conducted using PubMed, Scopus, Web of Science, and Google Scholar databases. 110 sources from high-impact factor journals were analyzed, including key randomized controlled trials (STICH, REVIVED-BCIS2), meta-analyses, and systematic reviews on ischemic cardiomyopathy and revascularization methods.Results. Ischemic cardiomyopathy is the leading global cause of heart failure, in the treatment of which revascularization plays an important role alongside quadruple pharmacotherapy. PCI demonstrates superior stroke risk reduction compared to CABG, while CABG excels in reducing repeat revascularization needs and improving long-term survival. In patients achieving complete revascularization, mortality risk decreased by 34% and repeat revascularization risk by 33%.Conclusion. When choosing between PCI and CABG in patients with ischemic cardiomyopathy, patient clinical characteristics, coronary anatomy, and comorbidities must be considered. The degree of revascularization and myocardial viability are important factors determining clinical outcomes.